The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2004
DOI: 10.1086/392501
|View full text |Cite
|
Sign up to set email alerts
|

Enterotoxin B Is the Predominant Toxin Involved in Staphylococcal Scarlet Fever in Taiwan

Abstract: This study retrospectively reviewed all pediatric cases of staphylococcal scarlet fever (SSF) that occurred during a 10-year period in a 1400-bed tertiary medical center in northern Taiwan. All 20 cases of SSF occurred in previously healthy individuals. Skin and soft-tissue infections predominated among children from whom Staphylococcus aureus was isolated. Polymerase chain reaction testing was used to detect known staphylococcal toxin genes, and of the isolates studied, most (18 [90%] of 20) contained only th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
7
0
2

Year Published

2009
2009
2019
2019

Publication Types

Select...
4
2
1

Relationship

0
7

Authors

Journals

citations
Cited by 20 publications
(10 citation statements)
references
References 20 publications
1
7
0
2
Order By: Relevance
“…Kenyan isolates bearing SEB typed to CC 8 and CC 152 consistent with previous observations where SEB was identified most often in CC8 isolates in New York [66]. A Taiwanese study identified SEB to be the cause of Staphylococcal scarlet fever [67]. In this study, SEB was detected in MSSA isolates obtained from a burn and from an abscess.…”
Section: Discussionsupporting
confidence: 88%
“…Kenyan isolates bearing SEB typed to CC 8 and CC 152 consistent with previous observations where SEB was identified most often in CC8 isolates in New York [66]. A Taiwanese study identified SEB to be the cause of Staphylococcal scarlet fever [67]. In this study, SEB was detected in MSSA isolates obtained from a burn and from an abscess.…”
Section: Discussionsupporting
confidence: 88%
“…aureus encodes numerous toxins, including pore-forming toxins, ETs, and superantigens (Grumann et al, 2014). The identified SSF-associated toxins are primarily superantigens, including SEA-D, SEG, SEI, TSST-1, and rarely, ETA and ETB (Courjon et al, 2013;Jarraud et al, 1999;Lina et al, 1997;Lo et al, 2009;Wang et al, 2004). The isolate from our case was only positive for SEM among the superantigens.…”
Section: Discussionmentioning
confidence: 63%
“…Staphylococcal scarlet fever (SSF) is characterized by an exanthem without enanthem, bullae, or exfoliation, and it is considered to be a mild form of SSSS or TSS (Courjon et al, 2013;Lo et al, 2009). SSF has never been reported in elderly patients, and an association between SSF and staphylococcal enterotoxin M (SEM) has not been published previously (Courjon et al, 2013;Lina et al, 1997;Lo et al, 2009;Wang et al, 2004;Weisse, 2001). Thus, to our knowledge, we report the first case of an elderly patient with SSF caused by SEM, which was associated with a case of otitis externa.…”
Section: Introductionmentioning
confidence: 81%
See 1 more Smart Citation
“…The clinical S. aureus isolates were obtained from the Tri‐Service General Hospital (Lo et al, ; Wang, Lo, Hsu, & Chu, ). Disease‐causing S. aureus strains (S) were isolated from skin wounds resulting from abscesses, bullous impetigo, or carbuncles; some patients suffered from generalised skin rashes excluding streptococcal infection.…”
Section: Methodsmentioning
confidence: 99%